Update on anti-tumor necrosis factor agents and other new drugs for inflammatory bowel disease. (19th June 2017) - Cohen, Benjamin L; Sachar, David B
Abstract : The treatment of inflammatory bowel disease (IBD)—ulcerative colitis (UC) and Crohn's disease (CD)—has evolved beyond surgery with the introduction of biologic agents, primarily antibodies against mediators of inflammation and cell attraction. Anti-tumor necrosis factor (TNF) agents have been the first line treatment for moderate to severe ulcerative colitis and Crohn's disease for more than 15 years. During that time much has been learnt about how best to use these agents. This review will assess the evidence on how to optimize the use of anti-TNF agents; when and how to start treatment; how to monitor treatment and when to de-escalate it; and the potential adverse effects of these drugs. New and emerging treatments such as anti-attractants, anti-interleukins, and Janus kinase (JAK) inhibitors will also be discussed.